Tuberous Sclerosis or Bourneville-pringle disease: A rare case report - Kumar Veshar, Harsh; Veer Bahadur Singh,; Mayank Shrivastava,; Ibrahim Khan,; Kapil Singh Meena,; Sourabh Soni,; Amit Kant,; Singh , Saranshi (International Journal of Medicine, 2023)
Introduction: Tuberous sclerosis or Bourneville’s disease is rare autosomal dominant neurocutaneous. Which is characterized by Skin changes, neurological issues, and the development of hamartomas in several organs that cause morbidity and mortality. The gingival hyperplasia, fibromas, hypopigmented lesion’s and enamel hypoplasia are the most typical features of presentation. The case report emphasises on the crucial clinical characteristics, radiographic characteristics, and laboratory abnormalities of Tuberous Sclerosis assisting in the early detection and treatment of such a rare illness.Case presentation: In this report, we present a case of tuberous sclerosis in a 25-year- old female who displayed abnormal body movement along with a hypopigmented macule, ash leaf spots, periungual fibroma, gum hyperplasia, and hematuria with pain in the bilateral flank.Conclusion: Our aim is to raise awareness for tuberous sclerosis by using this instance to highlight the disease's rarity and the difficulty in identifying and treating cases like this.